Powder injection moulded Ti6Al4V-HA composite for implants - Nurul Nadiah Mahmud,; Abu Bakar Sulong,; Ameyama, Kei (Penerbit Universiti Kebangsaan Malaysia, 2023)
Powder injection moulding (PIM) is widely used to produce complex shapes of Titanium and its alloys. Ti6Al4V-HA feedstocks at 63, 64 and 66 vol.% were produced by combining a Ti6Al4V-HA powder mixture (90:10 wt.%) with a binder system containing palm stearin (PS) and low-density polyethylene (LDPE). Binder system consisted with 60 wt.% of PS and 40 wt.% of LDPE. All powder loading materials were successfully injection moulded into the shape of a tension bar. Following that, all powder loadings were successfully debound in solvent and thermal methods. Based on SEM observation that 66 vol.% powder loading demonstrated homogenized distribution of powder and binder. Hence, 66 vol.% powder loading was selected for further process sintering at 1300 ºC, and its bending strength was evaluated. Sintered Ti6Al4V-HA with porous structure has Young’s modulus of 11 GPa, within the Young modulus of bone (10 to 30 GPa). The results of this study indicate that sintered Ti6Al4V-HA has potential as an implant material.